Analisis Pembiayaan Sektor Konstruksi Pada Perbankan Syariah di Indonesia - Nidaa Nazaahah Kusumawati (Department of Islamic Economics, IPB University, 2013)
The construction sector is an important sector in supporting development projects in Indonesia. The development of the construction sector requires the role of the banking sector to provide access of capital through credit. This study aims to analyze the relationship among factors of banking performance, monetary instruments, macroeconomic condition and rate of return towards construction financing in Islamic banking industry. This study uses Vector Error Correction model with monthly data from 2006 until 2012 as its method of analysis. The study finds that the ratio of construction financing responds positively to the shock of Financing to Deposit Ratio (FDR), the interest rate of SBI (SBI), Industrial Production Index (IPI), inflation rate (INF), and equivalent rate of financing (ERP). While shocks of the Third Party Funds (DPK), lending rates (SBK), non performing financing (NPF), fee of SBIS (BSBIS), and the placement of funds in PUAS (PUAS) variables are responded negatively. Islamic bank should be able to be more focused on construction financing as it will contribute to the development of real sector and national income. In addition, Islamic bank should have more concern on assesment criteria to choose borrowers in order to reduce the amount of non performing financing.